Współczesny uniwersytet - w pułapce racjonalności eksplikatywnej = Modern university - in the trap of explanatory rationality - Żywczok, Alicja (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The disparity between the classic model of pursuing science and explanatory rationality inspired the author to analyze the sources of researchers` concern about preserving an appropriate level of science culture. The author questions the selected directions of development (vs. involution) of modern universities, exposing their apparent modernity (e.g. parametric reporting and categorization) that lead to an instrumental treatment of researchers, research and teaching employees, as well as of science itself (understood as a discipline of culture).
Keywords: uniwersytet; nauka; rozum eksplikatywny; rozum implikatywny; parametryzacja; university; science; explicative mind; implicative mind; parametrization